Aprotinin Does Not Inhibit the Release of PGI2 or vWF from Cultured Human Endothelial Cells - Royston, B D; Royston, D; Coade, S B; Morgan, D M L; Pearson, J D (Thrombosis and Haemostasis, 1992)
The release of prostacyclin (PGI2) and von Willebrand factor (vWF) from human umbilical vein endothelial cells (HUVEC) was examined to determine if aprotinin had any effects on these endothelial cell reactions. These end-points were chosen to indicate if this serine protease inhibitor caused alterations in the control of haemostatic function by endothelium, in the light of the improvement in haemostasis seen in patients given aprotinin therapy at the time of open heart surgery. Stimuli used to promote secretion of prostacyclin and vWF were human α-thrombin, histamine, protamine sulphate, poly-L-lysine and phor-bol myristate acetate. Aprotinin (30 pM) had no significant effect on the basal or stimulated release of PGI2 or vWF from HUVEC.